Indentifikasi Gaya Bahasa Pada Novel â€œThe Antogonist Projectâ€ Karya Aranindy - Rachel, Marshella; Nensy Megawati Simanjuntak (Kopula: Jurnal Bahasa, Sastra, dan Pendidikan, 2024)
Literary works are art in the form of writing or oral that has beauty value in it. Novels are one of the literary works that are popular with teenagers, both physical and electronic fiction stories are still popular. Popular novels include novels with the romance, teen fiction, fan fiction and action genres set in everyday life. This means that the imagination or thoughts expressed are not excessive and still make sense. Apart from an interesting plot, the characteristics and characteristics of the author in presenting his work are also an additional point for teenagersâ€™ interest in reading novels. Therefore, this research was conducted to determine the elements contained in the novel. The aim is to provide insight and knowledge regarding the language styles contained in the novel â€œThe Antagonist Programâ€ by Aranindy, so that in future research on the same subject it can be used as material for consideration. The research method used is descriptive qualitative. Where in the process of collecting data using observation and documentation as well as analysis of language style elements in the novel â€œThe Antagonist Programâ€ by Aranindy.